New species of Graphidaceae from Loei Province, Thailand - Poengsungnoen, Vasun; Manoch, Leka; Mongkolsuk, Pachara; Kalb, Klaus (Phytotaxa, 2014)
Twelve new species of the lichen family Graphidaceae are described from NE Thailand, namely Fissurina niveoalba, with warty paraphyses tips, muriform ascospores and the lack of secondary lichen substances; F. phuluangii, with 2–8 muriform ascopores and the production of stictic and hypostictic acids; Graphis subdussii, distinguished by unbranched, straight ascomata with entire labia, a completely carbonized exciple and transversely septate, up to 170 µm long ascospores; G. subinsulana, with conspicuous, prominent ascomata, a laterally carbonized exciple, single, muriform ascospores and norstictic acid; Leiorreuma hypomelaenoides, which differs from L. hypomelaenum by the absence of hypostictic acid; Phaeographis caesiodiscoides, distinguished by radiately branched immersed to erumpent ascomata with uncarbonized exciple and muriform, brown ascospores; P. loeiensis with numerous irregularly branched, clustered ascomata, with an uncarbonized exciple and 8–11-septate brown, transversely septate ascospores; P. neotricosoides which differs from P. neotricosa by the lack of neotricone, instead producing stictic acid; P. phurueaensis, distinguished by a clear hymenium, 5–7-septate, dark-brown ascospores and especially by producing stictic and norstictic acids, both as major metabolites; P. schizolomoides, distinguished by conspicuous prominent ascomata with a white-pruinose disc surrounded by a whitish thalline margin, and brown, submuriform ascospores; P. siamensis, which is separated from P. brasiliensis by the production of stictic acid and small, 3-septate ascospores; and Platygramme subarechavaletae, which is distinguished by inconspicuous ascomata with a concealed disc, an apically to laterally carbonized exciple and submuriform ascospores.